2019
DOI: 10.1093/condor/duy013
|View full text |Cite
|
Sign up to set email alerts
|

Nesting near road edges improves nest success and post-fledging survival of White-rumped Shamas (Copsychus malabaricus) in northeastern Thailand

Abstract: Road edges in the temperate zone often negatively affect reproductive success, post-fledging survival, and dispersal of forest birds through processes associated with edge habitats. This pattern is less clear in the tropics due to a lack of studies using natural nests and radio-tagged fledglings as well as an almost complete absence of information on nest and fledgling predators. We investigated the influence of road edge on nest success, post-fledging survival, and dispersal of White-rumped Shama (Copsychus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…The BIC values can be compared with the previous Model 4 (BIC = 14,297) using the last column in the taxa (e.g. Angkaew, Sankamethawee, Pierce, Savini, & Gale, 2019;Hansen, Sato, Michael, Lindenmayer, & Driscoll, 2019;Valentine, Apol, & Proppe, 2019). Conversely, other studies have reported the reverse pattern, with lower predation risk in edge habitats relative to core sites (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The BIC values can be compared with the previous Model 4 (BIC = 14,297) using the last column in the taxa (e.g. Angkaew, Sankamethawee, Pierce, Savini, & Gale, 2019;Hansen, Sato, Michael, Lindenmayer, & Driscoll, 2019;Valentine, Apol, & Proppe, 2019). Conversely, other studies have reported the reverse pattern, with lower predation risk in edge habitats relative to core sites (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not unprecedented for a bird species to benefit from being close to disturbance. The White-rumped Shama (Copsychis malabaricus) had both higher nest success and postfledging survival at nest sites nearer to road edge in Asia (Angkaew et al 2019). Although we did not study nesting, the White-rumped Shama study suggests that birds in our study area could also receive some fitness benefit from nesting closer to disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Our study attempts to gain insight into the free-ranging and foraging ecology of this primary nest predator as a follow up to the research by Khamcha et al . (2018) and Angkaew et al . (2019) within the same study site.…”
Section: Introductionmentioning
confidence: 97%
“…(2018) reported that snakes were responsible for 34% of predation events on 287 monitored nests. More specifically, data suggest that Green cat snake Boiga cyanea is the dominant snake nest predator in the seasonally wet and dry evergreen forests of Northeast Thailand (Angkaew et al, 2019; Khamcha et al, 2018; Khamcha and Gale, 2020; Pierce et al, 2020). Despite the evidence of Southeast Asian snakes– particularly that of nocturnal, arboreal species (Donald et al, 2009; Pierce et al, 2020; Pierce and Pobprasert, 2013)– as nest predators, little to no research exists assessing their movement ecology.…”
Section: Introductionmentioning
confidence: 99%